2008
DOI: 10.12973/ejmste/75359
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Education in New Zealand

Abstract: Laboratory work is one of the main forms of teaching used in chemistry, physics, biology and medicine. For many years researchers and teachers have argued in favor or against this form of education. Student opinion could be a valuable tool for teachers to demonstrate the validity of such expensive and work intensive forms of education as laboratory work. However, due to concerns regarding overly positive replies and a strong personal bias in opinions regarding various courses, teachers and technicians, student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Consequently, further research is necessary across different countries and year levels. We also note a New Zealand study that found direct questioning of students resulted in them overestimating the strength of their opinions (Borrmann, 2008), in similar laboratory conditions to this study. Additionally, the fact that the data came from many different lab programs across multiple institutions and disciplines meant that the format of the laboratory notes could not be controlled.…”
Section: Limitations Of This Studysupporting
confidence: 71%
“…Consequently, further research is necessary across different countries and year levels. We also note a New Zealand study that found direct questioning of students resulted in them overestimating the strength of their opinions (Borrmann, 2008), in similar laboratory conditions to this study. Additionally, the fact that the data came from many different lab programs across multiple institutions and disciplines meant that the format of the laboratory notes could not be controlled.…”
Section: Limitations Of This Studysupporting
confidence: 71%
“…[4] Deacon stated that "the availability of tools can influence the process of learning at laboratory" [5]. Borroman (2008: 18) argued that "laboratory based-learning can improve the understanding of learning by the students" [6]. One of the materials is related to electricity and magnetism is magnetic induction of a solenoid.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, through examination of the chemistry laboratory experiences of current prospective biology teachers, it is important to reconsider the existing laboratory process and recommend new policies where necessary to improve the conditions for future prospective teachers. Few studie s have evaluated the implementation and working conditions in chemistry labs for prospective chemistry and science teachers and students (Ayas et al, 2002;Borrmann, 2008;Karamustafaoğlu, 2000;Polles, 2006;Rigano & Ritchie, 1994 2001). However, no study has yet evaluated the chemistry laboratory experiences of prospective biology teachers.…”
Section: Introductionmentioning
confidence: 99%